Zoledronic Acid and Skeletal Complications in Patients With Solid Tumors and Bone Metastases: Analysis of a National Medical Claims Database - Hatoum, Hind T. (2008)
BACKGROUND: Bone is among the most common sites of metastasis in patients with advanced cancer, and the development of bone metastases places patients at increased risk for skeletal complications. METHODS: This retrospective claims analysis included only patients with a diagnosis of bone metastasis who had a single type of solid tumor of the breast (women), prostate, or lung and experienced ≥1 skeletal complication between January 2002 and October 2005. RESULTS: The mean follow-up (±standard deviation) for zoledronic acid (ZA)-treated patients versus untreated patients was 12.2 ± 9.05 months versus 8.7 ± 9.28 months, respectively (P <.001). The monthly rate of skeletal complications in ZA-treated patients versus untreated patients was 0.29 ± 0.3 per month versus 0.43 ± 0.4 per month, respectively (P <.001). Persistent ZA use was associated with longer follow-up duration (P <.05) and a greater probability of continuing follow-up. Greater persistency was associated with lower monthly rates of skeletal complications (P <.05). The length of follow-up for ZA use according to the recommended dosing schedule was 17.11 months compared with 9.93 months for nonrecommended schedules and 8.68 months for no treatment (analysis of variance; P <.001). The rate of skeletal complications with ZA use on the recommended schedule was 0.16 events per month versus 0.31 events per month for nonrecommended schedules and 0.43 events per month for no treatment. In the subgroup analysis, the mean time to first complication was 185 ± 210 days in the ZA-treated group versus 98 ± 161 days in the untreated group (P <.0001). The mean time from the first complication to the second complication was 111 ± 124 days in the ZA-treated group versus 86 ± 114 days in the untreated group (P <.05). CONCLUSIONS: Real-world evidence indicated that ZA reduced the skeletal morbidity rate and delayed the time to skeletal complications.